EVALUASI PROSES PEMBELAJARAN PJOK DI SMK AGRIBISNIS KOTA BENGKULU - Lahia, Ilham; Perdima, Feby Elra; Sumantri, Ajis (Journal Of Dehasen Educational Review, 2023)
This study aims to determine the implementation of evaluation in the learning of Physical Education, Sports, and Health at Agribusiness Vocational Schools in Bengkulu City. This research is a descriptive research. The method used is a survey with data collection techniques using a questionnaire in the form of a closed questionnaire. The subjects in this study were PJOK students at SMKN Agribusiness Bengkulu City. Data analysis techniques using quantitative descriptive analysis as outlined in the form of percentages. The results showed that the implementation of the PJOK evaluation at the Agribusiness Vocational School of Bengkulu City based on the assessment aspect factors in PJOK learning was in the category of "very poor" at 0% (0 teachers), "poor" at 33.33% (8 teachers), "adequate" at 25.00% (6 teachers), "good" at 25.00% (7 teachers), and "very good" at 16.67% (4 teachers). The conclusion of the research evaluation of physical education learning is in the Less category.